Fenomena Local Bossism Dalam Distribusi Bahan Bakar Minyak Solar di Pelabuhan Perikanan Nusantara Sungailiat - Nurul Rahma; Ibrahim; Ranto (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The phenomenon of local bosses is mostly related to electoral politics. Even though when discussing the problem of local bossism or local bosses, it is often found on issues that are often considered small and trivial even though they have a very large impact on society, where this local bossism is a very complicated and varied political study, such as the problems distribution of diesel fuel at the Nusantara Fishing Port of Sungailiat. The purpose of this research is to analyze the phenomenon of local bossism in the distribution of diesel fuel at the Nusantara Fishing Port of Sungailiat and to identify the factors behind it. This study uses the concept of Local Bossism by John Thayer Sidel as the main theory in research and the concept of Rent Seeking by Gurdon Tullock and Anne Kruger as an additional theory. The method used in this research is descriptive qualitative, the primary data source comes from unstructured interviews by interviewing local bosses, fishermen, and employees (state apparatus). The results of this study indicate that the presence of local bossism in the distribution of diesel fuel at the Nusantara Fishing Port of Sungailiat is a product resulting from the conspiracy and collusion of the state apparatus with local bosses. What arises from the existence of power possessed by the state apparatus and the "social authority" that exists in local bosses in controlled communities is what causes bosses or bossism to emerge and continue to grow as local political forces. The factors behind the phenomenon of local bossism are (1) the strong position of local bosses, (2) protection from state apparatus and state apparatus, and (3) community dependence on local bosses.